Acompañamiento como pasante de ingeniería civil en actividades de secretaría de infraestructura en la alcaldía de Duitama - Boyacá (2023)
Road infrastructure is essential for the development of any municipality, not only optimizes accessibility to places, but also improves pedestrian safety. In the municipality of Duitama, the student has the opportunity to promote the improvement of the construction processes through an internship at the infrastructure secretary's office, participating in the infrastructure, participating in the support in the planning and control of road infrastructure contracts. road infrastructure contracts. Throughout the document, the activities carried out are described in detail, including photographic records and work quantity control forms, working on different types of pavements, including flexible pavement, footprint and cobblestone.